Pengawasan digital terhadap anak usia dini berbasis peran masyarakat: studi kasus di desa pandansari lor, kecamatan jabung, kabupaten malang - Saida, Mukhammad Fahmi Ulum (Maliki Interdisciplinary Journal, 2026)
The rapid development of digital media has significantly influenced the daily lives of early childhood, including those living in rural areas. This condition requires digital supervision that is not only the responsibility of parents but also involves the collective role of the community. This study aims to analyze community-based digital supervision of early childhood in Pandansari Lor Village, Jabung District, Malang Regency. This research employed a qualitative approach using a case study method. Data were collected through observations, in-depth interviews, and documentation involving parents, community leaders, and village officials. The results indicate that digital supervision of early childhood is implemented through digital parenting practices, such as limiting the duration of digital media use, monitoring content, and encouraging non-digital activities within the child’s social environment. The role of the community is reflected in social control, communication among residents, and collective agreements regarding children’s use of digital media. However, the implementation of digital supervision still faces challenges, particularly the limited understanding of digital media impacts on early childhood development among some community members. This study concludes that community-based digital supervision has the potential to support healthy digital parenting when accompanied by continuous digital awareness and education.